Examination of school children’s threshold exposure duration for recognition of test objects (TEDRTO) for assessment of their visual fatigue (Ukrainian Journal of Ophthalmology, 2026)
Background: Due to increased visual load during schooling, it is important to use a methodology for assessment of visual fatigue in children which would be understandable to them and which would not require much time.Purpose: To analyze the potential of using Threshold Exposure Duration for Recognition of Test Objects (TEDRTO) measurements for the assessment of the effect of gradual visual load on the functional status of the visual system in children of school age.Materials and Methods: A special device was used to assess the effect of gradual visual load on the functional status of the visual system. The examination procedure lasted 3-4 minutes for each child. Fifty seven children (aged 13 to 17 years) with a visual acuity of 1.0, orthophoria, ophthalmoscopically normal fundi, and emmetropic refraction were examined before and after a gradual visual loading task. Their task incorporated a conventional visual load; they were to type on a computer for 30 minutes using 14-pt, Тimеs New Roman font.Results: Binocular TEDRTO values increased significantly after the visual loading task (Wilcoxon rank test; for exposures of white, red or green test object, p = 0.000027, p = 0.000040 and p = 0. 000040, respectively).Conclusion: If implemented into practice, the methodology could help to identify visual fatigue timely, and to outline fatigue prevention measures.
Keywords: expositional visual acuity; visual fatigue